1994
DOI: 10.1111/j.1365-2621.1994.tb06914.x
|View full text |Cite
|
Sign up to set email alerts
|

Roasting Effects on Dietary Fiber Composition of Cocoa Beans

Abstract: The effect of roasting on dietary fiber fractions of cocoa beans was determined by gravimetric and fractionation procedures after enzymatic treatment. Roasting had no notable effect on total dietary fiber content (TDF). Components of insoluble dietary fiber (IDF) became redistributed after roasting. One of the largest changes was a sharp increase of Klason lignin. The noted decrease in sugar content without a change in IDF suggested that neutral sugars and uranic acids may be involved in Maillard polymer forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
(4 reference statements)
3
3
0
Order By: Relevance
“…In this specific matrix, Maillard reaction products such as melanoidins, which are not completely cleaved by hydrolysis, may largely contribute to Klason lignin contents. This observation was previously described by Valiente et al, who determined Klason lignin contents in green and roasted coffee beans [53].…”
Section: Lignin As Insoluble Dietary Fiber Constituentsupporting
confidence: 77%
“…In this specific matrix, Maillard reaction products such as melanoidins, which are not completely cleaved by hydrolysis, may largely contribute to Klason lignin contents. This observation was previously described by Valiente et al, who determined Klason lignin contents in green and roasted coffee beans [53].…”
Section: Lignin As Insoluble Dietary Fiber Constituentsupporting
confidence: 77%
“…The slight difference between the flour and chia seeds' dietary fiber content is that chia flour is made through a delicate physical process, namely roasting for approximately 6 minutes and grinding by a blender did not significantly decrease dietary fiber. Furthermore, in line with the research by Valiente et al (1994) roasting process does not affect the total dietary fiber of cacao beans, insoluble dietary fiber will be redistributed following roasting dissolved food does not show a considerable variation. Besides, the research conducted by Haripriya and Aparna (2018) showed that the increase of total dietary content was 17.61% of the chia flour as the dry roasting result.…”
Section: Resultssupporting
confidence: 75%
“…The roasting process had no significant effect on crude fiber content (p>0.05). Supporting results were obtained in the study which investigated the effects on roasting on fiber contents of cocoa beans (Valiente et al, 1994).…”
Section: Proximate Compositions Of Unroasted and Fluidized Bed Roasted Longan Stone Powderssupporting
confidence: 65%